Analysis of k-means clustering algorithm in advanced country clustering using rapid miner - Prabaswara, Ireneus; Pertiwi, Dwika Ananda Agustina; Jumanto, Jumanto (SHM Publisher, 2024)
In the era of globalization, the understanding of developed countries is no longer limited to the level of per capita income alone. As part of the analysis of developed countries based on aspects of government revenue, income balance, national savings, and domestic output based on sales. This research aims to cluster and to find out how these economic indicators are interrelated and affect the status of a country as a developed country. The K-means algorithm is used to identify patterns of countries with similar economic characteristics. From the research conducted, there are 4 clusters generated based on the characteristics of developed countries.